Penerapan Pendekatan ADLX (Active Deep Learner Experience) dalam Pembelajaran PAI: Studi Kasus pada Praktik Pembiasaan Sholat di SD Negeri 1 Mantingan - Dwiva Zumarul Muna; Nusrotus Sa’idah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study seeks to investigate the implementation of the ADLX approach in Islamic Religious Education (PAI), particularly focusing on the practice of habituation to prayer. By incorporating the TERPADU principles, the research explores how this learning method can actively enhance student participation and deepen their comprehension. This study was carried out at SD Negeri 1 Mantingan employing a qualitative research method with a case study approach. The sample included one educator and third-grade students. Data were collected through observation, interviews, and documentation. Data analysis was performed using the data triangulation technique to ensure validity. Based on the results of the study conducted at SD Negeri 1 Mantingan, the implementation of the ADLX approach in the practice of sholat habituation proved effective in enhancing students' active engagement, spiritual awareness, and character development. This approach provides an applicative, contextual, and reflective learning experience by directly involving students in the practice of sholat, group discussions, and reflection on religious values. By integrating the TERPADU principle and a gradual learning strategy, the process addresses not only cognitive aspects but also the affective and psychomotor domains, fostering enthusiasm, discipline, and students' concern in performing religious practices.